Regression of Liver Steatosis Following Phosphatidylcholine Administration: A Review of Molecular and Metabolic Pathways Involved - Osipova, D.; Kokoreva, K.; Lazebnik, L.; Golovanova, E.; Pavlov, Ch.; Dukhanin, A.; Orlova, S.; Starostin, K. (Frontiers in Pharmacology, 2022)
Liver steatosis is a key pathology in non-alcoholic or metabolic associated fatty liver disease. Though largely ignored for decades it is currently becoming the focus of research in hepatology. It is important to consider its origin and current opportunities in terms of pharmacotherapy. Essential phospholipids (EPLs) rich in phosphatidylcholine (PCH) is a widely used treatment option for fatty liver disease, and there is a solid amount of consistent clinical evidence for the regression of steatosis after treatment with EPLs. As knowledge of PCH (a key component of EPLs) pharmacodynamics and mode of action driving this widely observed clinical effect is currently insufficient, we aimed to explore the potential molecular and metabolic pathways involved in the positive effects of PCH on steatosis regression.